Logos (bio)politikon:: Literary fiction as power over signification - Amores Fúster, Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The aim of this article is to construct a structural theoretical analogy between animality-factuality and humanity-fictionality. In order to do so, a double hypothesis will be defended. On the one hand, the biological predetermination that dominates animal’s existence will be identified with the significant predetermination that also dominates factual discourses. And on the other hand, the virtually infinite potentiality that characterizes human’s existence will be identified with the also virtually infinite signifying power of literary fictional expression. Thus, and taking as reference both the Aristotelian definition of the human being as zoon politikon and the Foucaultian conception of the biopolitical subject, we will characterize literary fiction as logos (bio) politikon, that is, as that discourse in whose singular rules of meaning it is questioned its very condition of significant discourse.